Simulating the Various Subsystems of a Coal Mine - Okolnishnikov, V.; Rudometov, S.; Zhuravlev, S. (Engineering, Technology & Applied Science Research, 2016)
A set of simulation models of various subsystems of a coal mine was developed with the help of a new visual interactive simulation system of technological processes. This paper contains a brief description of this simulation system and its possibilities. The main possibilities provided by the simulation system are: the quick construction of models from library elements, 3D representation, and the communication of models with actual control systems. These simulation models were developed for the simulation of various subsystems of a coal mine: underground conveyor network subsystems, pumping subsystems and coal face subsystems. These simulation models were developed with the goal to be used as a quality and reliability assurance tool for new process control systems in coal mining.